Developing Solid Oral Dosage Forms : Pharmaceutical Theory & Practice. - Qiu, Yihong (Elsevier, 2008)
The essential principles of physical pharmacy, biopharmaceuticals and industrial pharmacy as well as various aspects of state-of-the-art techniques and approaches in pharmaceutical sciences and technologies.